Principles of form and design - Wong, Wucius (New York, NY John Wiley & Sons, Inc., 1993)
Wucius Wong's books on design principles have become classics in art and design education programs around the world. In this guide, Wong combines three of his classics into one convenient master class in the principles and practical fundamentals of design.

Divided into three major sections, the guide:

>Provides a solid foundation in design basics, with emphasis on flat, abstract forms

>Demonstrates the creatin of forms, focusing on representational aspects that extend the designer's visual vocabulary

>Examines the use of linear and planar materials for constructing free-standing objects in reality

Explanations of two-dimensional and three-dimensional design basic have been integrated with the latest concepts of computer graphics. Wong covers the equipment and software that suit a designer's requirements, then discusses how to use the computer to implement design principles addressed in the rest of the book.

The interrelationships of different design dimension are clarified with almost 900 diagrams and illustrations presented in a large-page format. An up-to-the-minute glossary has also been incorporated to help readers keep up with the latest terminology.

A source of broad scope from one of today's most influential design writers, Principles of Form and Design will meet the needs of all graphic artists and designers.
Includes index
FA-3597g - Donated by Prof. Tina P. Colayco
Keywords: Computer-aided design